WEB 2.0 MEDIATED COLLABORATIVE WRITING IN EFL CONTEXT: SURVEY OF EMPIRICAL RESEARCH - Yaniafari, Rahmati Putri (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
The existence of Web 2.0 technology which allows all users to meet, read, and write online provides room for innovations in teaching and learning method. Online collaborative writing tools, a type of the social networking web 2.0, has been increasingly integrated into English language teaching and learning. A number of researches have been conducted to examine the use of this online collaborative writing.